The Role of Glutamatergic Dysfunction in Treatment-Resistant Obsessive-Compulsive Disorder: Treatment of an Adolescent Case with N-Acetylcysteine Augmentation - Yazici, Kemal Utku; Percinel, Ipek (Mary Ann Liebert, Inc, 2014)
[Abstract Not Available]
Keywords: Methodological Issues; Acetyl Cysteine; Children